Novel source for formulation of nutritious fish feed - Jamal, Parveen; Ilias, Nurul Najihah; Jaswir, Irwandi; Sulaiman, Sarina (2015)

(untitled)
The rising cost of imported fish feed ingredients has called for an intensive research towards the production of high nutritional fish feed using cheap and natural nutrient sources. In this study, seaweed and palm kernel cake were used as alternative protein ingredients in fish feed and the enrichment of its nutritional value was achieved by using solid state fermentation. The fish feed is the bioprotein (final product) produced after the solid state fermentation. The feed has undergo several screening and optimization process in order to obtain the appropriate media and process conditions to produce an optimum bioprotein concentrations in the final product. Analysis of the final product has been conducted and tested on fish to identify its effect on fish performance. Hence, this study has produced the enhanced fish feed with high nutritional compounds (especially protein).